2020
DOI: 10.1186/s40164-020-00187-x
|View full text |Cite
|
Sign up to set email alerts
|

Advances of target therapy on NOTCH1 signaling pathway in T-cell acute lymphoblastic leukemia

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is one of the hematological malignancies. With the applications of chemotherapy regimens and allogeneic hematopoietic stem cell transplantation, the cure rate of T-ALL has been significantly improved. However, patients with relapsed and refractory T-ALL still lack effective treatment options. Gene mutations play an important role in T-ALL. The NOTCH1 gene mutation is the important one among these genetic mutations. Since the mutation of NOTCH1 gene is considered as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 66 publications
0
24
0
1
Order By: Relevance
“…Due to the high prevalence and importance of NOTCH1 activating mutations in T-ALL, targeted therapy on NOTCH1 pathway has been a major interest. This includes γ-secretase inhibitors (GSIs), ADAM inhibitors, SERCA inhibitors, and monoclonal antibodies [180]. Among them, GSIs, that block the activation process of NOTCH receptors by inhibiting proteolytic cleavage, have been tested in preclinical and Phase 1 studies [181,182].…”
Section: Notch1 Activating Mutations In T-allmentioning
confidence: 99%
“…Due to the high prevalence and importance of NOTCH1 activating mutations in T-ALL, targeted therapy on NOTCH1 pathway has been a major interest. This includes γ-secretase inhibitors (GSIs), ADAM inhibitors, SERCA inhibitors, and monoclonal antibodies [180]. Among them, GSIs, that block the activation process of NOTCH receptors by inhibiting proteolytic cleavage, have been tested in preclinical and Phase 1 studies [181,182].…”
Section: Notch1 Activating Mutations In T-allmentioning
confidence: 99%
“…While NOTCH1/FBXW7 cannot be used alone as prognostic markers, there is a general agreement in considering the NOTCH signaling as a good candidate for tailored therapy. Preclinical studies have shown a strong therapeutic effect of different NOTCH1 inhibitors, such as γ-Secretase (GS) and ADAM (Disintegrin Metalloproteases) inhibitors, monoclonal antibody, and molecules that block the activity of the NOTCH1 transcription factor complex, in both T-ALL cell lines and primary samples [68]. In addition, therapeutic targeting of the E3 ubiquitin ligase SKP2, whose expression is regulated by NOTCH signaling, has been proven to block T-ALL proliferation in in vitro and in vivo models [69].…”
Section: Actionable Deregulated Pathways and Cellular Processes 61 Notch Pathway Activationmentioning
confidence: 99%
“…Additionally, a combination of GSIs and chloroquine has presented a synergistic effect in vitro on the T-ALL cell line and is associated with fewer side effects [40]. Using GSIs as a single agent seems to be insufficient in T-ALL carrying Notch1 mutations, and combined treatments, with reduced gastrointestinal toxicity and enhanced antileukemic effects, may be alternative options [41]. Apart from the limitations and constant improvements in GSI therapy, distinct approaches targeting the NOTCH signaling pathway have been developed, including ADAM10 and CAD204520 SERCA inhibitors.…”
Section: Novel Approach In T-all Treatmentmentioning
confidence: 99%
“…In addition, monoclonal antibodies against the NOTCH1 receptor have shown efficacy in preclinical trials. OMP-52M51, a monoclonal antibody produced by mice immunized by human NOTCH1 protein fragments, showed antitumor effects in a T-ALL cell line in vitro and in vivo in xenograft models [ 41 , 42 ].…”
Section: Novel Approach In T-all Treatmentmentioning
confidence: 99%